Effect of compensation management on employee performance at the St. Michael’s Catholic Hospital, Pramso - Tetteh – Annor, Larbi (2015)
A thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF BUSINESS ADMINISTRATION (HRM OPTION).